EXPERIMENTAL EVIDENCE FOR THE ANTIDIABETIC ACTIVITY OF CAJANUS CAJAN LEAVES IN RATS - Ezike, Adaobi C. (Medknow Publications & Media Pvt Ltd, 2010)
The antidiabetic activity of methanol leaves extract of Cajanus cajan (L.) Millsp. (Fabaceae) was studied in alloxan-diabetic and in oral glucose loaded rats. The acute toxicity and lethality (LD(50)) and the phytochemical analysis of the extract were also evaluated. The results showed that the extract (400 and 600 mg/kg) significantly (P<0.05) reduced fasting blood sugar of alloxan diabetic rats in a dose-related manner, with maximum hypoglycemic effect at 4 – 6 h. The extract (400 and 600 mg/kg) also significantly (P<0.05) suppressed the peak postprandial rise in blood glucose of normal rats by 101.8 and 57.40% respectively. Acute toxicity and lethality test of the extract in rats gave an oral LD(50) greater than 5 g/kg. The findings indicate that the leaves of C. cajan may be beneficial as an antidiabetic therapy.